2004
DOI: 10.1194/jlr.m300208-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Impaired expression of NADH dehydrogenase subunit 1 and PPARγ coactivator-1 in skeletal muscle of ZDF rats

Abstract: Type 2 diabetes has been related to a decrease of mitochondrial DNA (mtDNA) content. In this study, we show increased expression of the peroxisome proliferator-activated receptor-␣ (PPAR ␣ ) and its target genes involved in fatty acid metabolism in skeletal muscle of Zucker Diabetic Fatty (ZDF) ( fa/fa ) rats. In contrast, the mRNA levels of genes involved in glucose transport and utilization (GLUT4 and phosphofructokinase) were decreased, whereas the expression of pyruvatedehydrogenase kinase 4 (PDK-4), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 44 publications
3
34
0
1
Order By: Relevance
“…Other studies in insulin-resistant rodents have reported reduced expression of PGC-1␣ and other markers of mitochondrial metabolism in muscle (21)(22)(23)(24). The reason for the disparity in results is unclear but may be related to methodological factors such as diet composition, the length of high-fat feeding, or the particular muscle groups examined (i.e., quadriceps versus gastrocnemius bundle).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Other studies in insulin-resistant rodents have reported reduced expression of PGC-1␣ and other markers of mitochondrial metabolism in muscle (21)(22)(23)(24). The reason for the disparity in results is unclear but may be related to methodological factors such as diet composition, the length of high-fat feeding, or the particular muscle groups examined (i.e., quadriceps versus gastrocnemius bundle).…”
Section: Discussionmentioning
confidence: 57%
“…Studies (3,16 -20) have shown mitochondrial fatty acid oxidation and the activity of oxidative enzymes are elevated in muscle of fat-fed rats and obese Zucker rats. Equally, however, several recent studies (21)(22)(23)(24) in rodent models of insulin resistance have reported deficits in a variety of markers of mitochondrial metabolism in muscle.…”
mentioning
confidence: 99%
“…Diabetes is a strong risk factor for PAD, and PGC-1␣ is repressed in diabetic skeletal muscle in both rodents and humans (45)(46)(47), suggesting that PGC-1␣ insufficiency may predispose to, or worsen PAD. The data presented here, combined with our previous studies (26), suggest that the benefits of exercise in PAD may also in part be mediated by PGC-1␣.…”
Section: Discussionmentioning
confidence: 99%
“…We (10) and other researchers (11)(12)(13) have reported that insulin-resistant states are characterized by a reduction in skeletal muscle of peroxisome proliferator-activated receptor (PPAR)␥ coactivator-1 (PGC-1), the transcriptional coactivator driving the expression of many genes coding for proteins in mitochondria. PGC-1 was initially identified as a protein that interacted with PPAR␥ (14).…”
mentioning
confidence: 99%